System for acquisition and transmission of thermal images to monitor equipment of an electrical substation - Odair José Sanson Neto; Leonardo Göbel Fernandes; Alceu André Badin; Winderson Eugenio dos Santos; Eduardo Félix Ribeiro Romaneli (The Journal of Engineering and Exact Sciences)
Thermographic monitoring systems are achieving satisfactory results in identifying points with anomalous temperature, preventing faults to occur. In the development of a methodology for automatic analysis of thermal images, an automated system for data acquisition and transmission is necessary. This article aims to compare the different ways to acquire images from a thermal camera FLIR® A700: Atlas SDK, web interface and Rest API, among which the latter stands out because of its simplicity and easy implementation. The article also describes the developed software for automated capture of thermal images and the communication system developed to transmit these images.